Nutrition education and mastication improvement through social services provision in Ketapang sub-district, Probolinggo - Kresnoadi, Utari; Kamadjaja, Michael Josef Kridanto; Ari, Muhammad Dimas Aditya (Indonesian Journal of Prosthodontic, 2020)
Introduction: A community-based exercise was implemented with the specific theme â€œAwareness raising among Family Welfare Program and Youth Organization group members of the importance of Family Nutrition Literacy and of nutrition education and mastication improvement through provision of removable denturesâ€ in Ketapang sub-district, Kademangan district, Probolinggo. Aim: This community-based service was intended to inform the public of the importance of nutritional consumption to ensure a well-nourished family and enhanced mastication resulting from the use of removable dentures. This event was held in the middle of the COVID-19 pandemic. Methods: Two teams managing innovative and promotion were created. The role of the former was to conceptualize activities, while that of the latter was to directly inform the target community using a combination of printed and electronic media. These teams consisted of lecturers and 2nd year residents of the Department of Prosthodontics, Faculty of Dentistry, Universitas Airlangga. Results: The event involved the use of video conferencing through which residents delivered online counselling session to Family Welfare Program, Youth Organization group, and health cadre mem-bers who had already gathered at Ketapang Health Center, while maintaining physical distancing. Several residents worked on site alongside health cadres from the Ketapang Health Center. Given the ongoing pandemic, the teams decided to donate certain props: four full dentures, four removable partial dentures and four fixed partial dentures. Conclusion: Online counseling of the Ketapang Health Center cadres was expected to increase their awareness and comprehension of nutrition education and improvement in the mastication function of dentures through the use of teaching aids.